2019
DOI: 10.1029/2019gl084901
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Collapse Gravity Increase at the Summit of Kīlauea Volcano, Hawaiʻi

Abstract: We conducted gravity surveys of the summit area of Kīlauea Volcano, Hawaiʻi,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…The greatest improvement in SSR is thus the combination of the ellipsoidal source for the SCR with a point source for the HMMR. The location, just east of Halema'uma'u crater, and depth, about 1.5 km, of the HMMR source is consistent with previous studies (e.g., Baker and Amelung, 2012;Poland et al, 2014Poland et al, , 2019Anderson et al, 2015).…”
Section: Point Source Value [Confidence Interval]supporting
confidence: 91%
See 1 more Smart Citation
“…The greatest improvement in SSR is thus the combination of the ellipsoidal source for the SCR with a point source for the HMMR. The location, just east of Halema'uma'u crater, and depth, about 1.5 km, of the HMMR source is consistent with previous studies (e.g., Baker and Amelung, 2012;Poland et al, 2014Poland et al, , 2019Anderson et al, 2015).…”
Section: Point Source Value [Confidence Interval]supporting
confidence: 91%
“…Although common prior to 1983, intrusions beneath the summit area were rare after that time, and none had occurred since the advent of GNSS or Interferometric Synthetic Aperture Radar (InSAR), both of which can provide detailed observations of ground displacement. The 2015 episode, therefore, provides a unique opportunity to apply modern geodetic data sets and modeling techniques to improve our understanding of summit magmatism at Kīlauea, including interactions between the different parts of the magma plumbing system and the mechanisms for intrusive activity-information of vital importance as the volcano recovers from its 2018 collapse (Neal et al, 2019;Poland et al, 2019). Jo et al (2015) modeled COSMO-SkyMed InSAR data spanning the May 2015 summit intrusion and concluded that a volume change associated with the SCR explains their observations, but little other attention has been paid to this noteworthy event and its implications.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, the seismicity gradually increased again within a few days back to ∼40 events per day, much higher than the pre-eruption seismicity level in March. In addition, Poland et al (2019) suggested that both uplift and spreading were observed near the Pu'u'ō'ō vent, since the end of major eruptive activity in August 2018, which is roughly the same period we observed the increase of seismicity. Both our seismic and the geodetic observations indicate the post-eruption magma reservoir refilling occurred near Pu'u'ō'ō.…”
Section: Implications For the Eruption Processsupporting
confidence: 71%
“…Following the LERZ eruption, gradual inflation began at Kīlauea's summit, indicating continued magma recharge into the remnant shallow Halemaʻumaʻu reservoir (Poland et al 2019). Groundwater ingress into Kīlauea's vastly deepened summit caldera led to the growth of a water lake in 2019-2020 (Hsieh and Ingebritsen 2019;Ingebritsen et al 2021).…”
Section: Conclusion and Applications To Post-2018 Activitymentioning
confidence: 99%